Principles of mineral processing - Fuerstenau, Maurice C.; Han, Kenneth N. (Society for Mining, Metallurgy, and Exploration, 2003)
Annotation Comprehensive reference examines all aspects of mineral processing from the handling of raw materials to separation strategies to the remediation of waste products. Shows how developments in engrg., chemistry, computer science, and environmental science contribute to the ultimate goal of producing minerals and metals economically from ores.
Keywords: Ore-dressing.; Hydrometallurgy.; elektronické knihy; electronic books